Research trends in digital transformation in supply chain based on bibliometric and network analysis - Oh, Keontaek; Yoo, Hanna; Jeong, EuiBeom (Journal of Business Economics and Management, 2023)
With the development of the 4th Industrial Revolution technology, the digitalization of supply chain is also receiving a lot of attention. With various technological developments, the importance of digital transformation in a firm’s supply chain is increasing. Therefore, for a more comprehensive understanding of digital transformation in supply chain, we have implemented a rigorous systematic literature review by supplementing the shortcomings of existing literature and combining bibliometric analysis and network analysis with keyword network analysis. Using the SCOPUS database, we collected 182 papers addressing digital transformation in the supply chain published in renowned business administration journals, identified research trends. Then, we analyzed the connection of citations as well as the author’s keywords and their changes over time. Based on these results, this study presents the number of publications and changes in papers by period, influential authors and papers, key keywords and topics, etc. on digital transformation in supply chain. First published online 10 January 2024